Three new dimeric 2-(2-phenylethyl)chromones from artificial agarwood of Aquilaria sinensis. Issue 21 (2nd November 2021) - Xiang, Pan; Dong, Wen-Hua; Cai, Cai-Hong; Li, Wei; Zhou, Li-Man; Dai, Hao-Fu; Chen, Hui-Qin; Mei, Wen-Li
Abstract: Three new dimeric 2-(2-phenylethyl)chromones crassin I ∼ K (1 –3 ), together with one known analogue (4 ), were isolated from the artificial holing agarwood originating from Aquilaria sinensis . Their structures including the absolute configuration were elucidated by spectroscopic techniques (UV, IR, 1D and 2D NMR, ECD), and HRESIMS analysis, as well as by comparison with the literature data. Compounds 1 and 2 exhibited weak acetylcholinesterase inhibitory activity. Graphical Abstract: